PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPUTER OLEH PERANGKAT NAGARI DI KANTOR WALI NAGARI PELANGAI KACIAK KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Amarullah, Taufik Abdul Hasan; Ayu, Febriana Citra (STKIP Pesisir Selatan, 2020)
Many the village officer who does not have experience in information and computer area, it made their work does not finish on time. It was caused they did not know how to the usage of technology and computer well. The purpose of this research to explain the usage of computer technology by the officer of Pelangai Kaciak Village.This is descriptive research using qualitative approach, because the researcher took the data written and spoken, as informant of the research are the head of the village and his officer, 6 people. The data explained based on observation, interview, and documentation.The result of this research took from the information of the head of village and 6 his officer. From the interview can be explained that 1) the important application was used to accounting is SISKEUDES (Sistem keuangan desa/Village accounting system), SINAR was used to serve correspondence, Online tax was used to pay the people tax, MS. WORD was used to make the letter that there is not be in SINAR application, Excel application was used to SPJ and power point application was used perform material in internal meeting. 2) the problem of the usage the information and computer technology by the village officer was capacities of RAM, Lamp is often off, and slow loading of internet.